Unlocking Success: Nexus between Entrepreneurial Orientation and Financial Performance in Culinary MSMEs - Usil Sis Sucahyo; Theresia Woro Damayanti; Supramono Supramono (Journal of Economics, Business, and Accountancy Ventura, 2024)
This study aims to investigate the impact of entrepreneurial orientation on the financial performance of micro, small, and medium-sized enterprises (MSMEs) in the culinary sector, while also exploring the mediating roles of digital transformation and working capital in this relationship. Data were gathered via a field survey involving 360 culinary MSMEs operators in Semarang City, Salatiga City, and Surakarta City, with a proportional distribution across these locations. Statistical analysis was conducted using SEM-PLS. The results reveal that entrepreneurial orientation significantly influences financial performance, digital transformation, and working capital. Additionally, digital transformation and working capital play mediating roles in the relationship between entrepreneurial orientation and financial performance. This study contributes to theoretical insights by proposing a model to enhance the economic performance of culinary MSMEs, focusing on entrepreneurial orientation, digital transformation, and working capital. From a policy perspective, the government is encouraged to support various initiatives aimed at enhancing entrepreneurial capabilities, fostering the adoption of digital technologies, and promoting effective working capital management within the culinary MSMEs sector.